Plasma rich in growth factors and bone formation: a radiological and histomorphometric study in New Zealand rabbits - Francisco Molina-Miñano; Pía López-Jornet; Fabio Camacho-Alonso; Vicente Vicente-Ortega (Sociedade Brasileira de Pesquisa Odontológica, 2009)
A radiographic and histomorphometric study was conducted on the influence of autologous plasma rich in growth factors (PRGF) upon bone healing in surgically created defects in rabbits. Radiographically, bone regeneration was significantly greater with the use of PRGF after one month (p = 0.005), though no differences were recorded after the second month. In the histomorphometric analysis one month after surgery, the defects filled with autologous bone plus PRGF showed a greater percentage of neoformed bone (35.01 ± 5.31) than the control defects (22.90 ± 12.23), though the differences were not significant. Two months after surgery, the defects filled with autologous bone showed greater regeneration (46.04 ± 10.36%) than the control defects (30.59 ± 5.69%), though the differences were not significant. The application of PRGF in the bone defects produced in New Zealand rabbits exerted a limited effect on local bone formation.